Development of Skills Teaching Modules Writing (Schreibfertigkeit) German Level A2 GER. - Tarida Alvina Simanjuntak; Lydia Purba (CV Putra Publisher, 2026)
The German language learning process in today's era requires educators to be able to develop better teaching materials. The industrial revolution 4.0 requires educators to be more creative and innovative in implementing the learning and teaching process in the classroom. One of the supports for a good learning and teaching process is innovative teaching materials that increase students' knowledge. Specifically in German language learning, there are four skills that are the focus of learning: speaking, reading, writing, and listening. Speaking and writing skills are included as productive language skills, namely skills that can produce a work/product. Writing skills also require students to think creatively and innovatively. Writing skills (Schreibfertigkeit) cover linguistic material and also discuss various forms of texts/short discourses that at the A2 GER level correspond to themes that intersect with everyday life. In line with this, the development of teaching modules is one of the urgent matters in improving students' writing skills. Modules can foster student independence, because teaching modules contain materials and learning processes that will help students in understanding the learning. In line with that, it is hoped that this research aims to build students' self-confidence after the learning material can be learned from the module, because the teaching module delivered is very close and can be mastered correctly, and is expected to improve students' abilities in doing assignments related to writing skills. The approach in this study uses a qualitative and quantitative approach. The type of research used is a development research type with a 4D model, namely define, design, development, dissemination. The subjects of this study were all students of the German Language Education Study Program Semester 3 (three) HKBP Nommensen University Pematang Siantar. The data collection technique is by testing learning outcomes in accordance with the teaching material in learning writing skills (Schreibfertigkeit). The targeted output is publication in an accredited international or national journal